Negotiation strategies and offers : perceptions of mergers and acquisitions advisors - Paavola, Akseli (2014)
This thesis sought to identify mergers and acquisitions advisors’ perceptions of their own negotiation strategies in a typical negotiation. Additionally, the thesis examined the potential association between the first offer and a negotiator’s perception of his or her own negotiation strategy. This was researched empirically by presenting the negotiators two different first offer negotiation scenarios. In the first scenario, a buyer presented a first offer that was higher than a negotiator’s reservation value. In the second scenario, a buyer presented a first offer that was lower than a negotiator’s reservation value. The theoretical framework of the thesis was based on the negotiation analytic approach that was theoretically extended to the context of first offers and distributive and integrative negotiation strategies. Additionally, a quantitative and an expert based approach of negotiation research was used. The survey questionnaire, which measured the negotiators’ perceptions of integrative and distributive negotiation strategies and first offers, was created with a theory driven approach. Therefore, the survey questionnaires of previous research, such as the Dutch test, BPA II and five‐factor model was used as an example when this thesis’ questionnaire was created. The research data was gathered from a population of 300 professional advisors of mergers and acquisitions. The cross‐cultural sample of respondents comprised of 30 advisors. The responses were received from Europe, Americas and Asia‐Pacific. The data was analyzed by means of descriptive statistics, principal component analysis, reliability analysis, normality test and a paired samples t‐test. In line with the theoretic framework of the thesis and previous research results, this research suggests that a negotiator’s perception of his or her own negotiation strategy, in a typical negotiation, is more integrative than distributive. However, in terms of counteroffer strategies the thesis resulted in a contradictory descriptive finding. In both high and low offer scenarios, the majority of respondents’ perceived distributive strategy as their preferred strategy. A key finding of the thesis was that a first monetary offer in a negotiation was associated with a negotiator’s perception of his or her own negotiation strategy. This thesis concluded that a negotiator should use more integrative than distributive negotiation strategy. This strategy consist of behavior, which directs a negotiation towards a problem‐solving practice, where information sharing and trust is emphasized. In order to achieve this type of negotiation process, the negotiator should always make the first offer, for example, before the letter of intent phase. However, the negotiator should carefully analyze the potential reference values of the negotiating parties, create alternatives and evaluate consequences, in order to make trade‐offs. The alternatives could comprise of creative earn‐out models, vendors’ notes and third party negotiation models. However, the negotiator should acknowledge the high probability that an integrative first offer is countered with a distributive offer and communication strategy. Concerning negotiation goals, the negotiator should have a high level of aspiration, which in this context is the goal of high merger premium.